2015
DOI: 10.1016/j.ijgo.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Polypoid adenocarcinoma of the cervix during pregnancy managed with conservative treatment

Abstract: I. Zapardiel).Fig. 1. Magnetic resonance imaging showing a 16-mm cervical lesion (white arrow) in a woman at 25 weeks of pregnancy. (R. Malhas). Fig. 1. A benign serous cystadenofibroma after intraoperative drainage and oophorectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…From an oncological point of view, a systematic review totaling more than 600 cases confirmed an overall recurrence rate < 5% and a death rate < 3%, demonstrating the safety of this approach for small invasive cervical tumors [55]. RT in pregnancy has been investigated by many teams, as first-line therapy for patients diagnosed with tumors <2 cm (≤IB1 according to FIGO 2018) [33,[56][57][58][59][60][61][62][63][64][65][66] or, in rarer situations, for patients diagnosed with tumors >2 cm (≥IB2 according to FIGO 2018) [67][68][69][70][71][72][73][74][75]. RT can be performed either through abdominal [58][59][60]63,66,67,69,72,74,76] or vaginal approach (Dargent's method) [56,57,61,71,73,75,77,78], each technique being associated with its own advantages and drawbacks.…”
Section: Surgery Conization and Trachelectomymentioning
confidence: 97%
See 2 more Smart Citations
“…From an oncological point of view, a systematic review totaling more than 600 cases confirmed an overall recurrence rate < 5% and a death rate < 3%, demonstrating the safety of this approach for small invasive cervical tumors [55]. RT in pregnancy has been investigated by many teams, as first-line therapy for patients diagnosed with tumors <2 cm (≤IB1 according to FIGO 2018) [33,[56][57][58][59][60][61][62][63][64][65][66] or, in rarer situations, for patients diagnosed with tumors >2 cm (≥IB2 according to FIGO 2018) [67][68][69][70][71][72][73][74][75]. RT can be performed either through abdominal [58][59][60]63,66,67,69,72,74,76] or vaginal approach (Dargent's method) [56,57,61,71,73,75,77,78], each technique being associated with its own advantages and drawbacks.…”
Section: Surgery Conization and Trachelectomymentioning
confidence: 97%
“…Cesarean-Radical Hysterectomy (CRH) vs. Delayed Radical Hysterectomy (RH) CRH was the preferred modality of surgical therapy across studies [56,59,68,. Its main indications were residual disease after radical trachelectomy, IB1 tumors in patients who do not wish to undergo fertility-preservation surgery, or for IB2-3 tumors after neoadjuvant chemotherapy (Figure 2).…”
Section: Surgery Conization and Trachelectomymentioning
confidence: 99%
See 1 more Smart Citation